Performance of Multilayer Composite Hollow Membrane in Separation of CO2 from CH4 in Mixed Gas Conditions - Zakariya, S. (MDPI, 2022)
Composite membranes comprising NH2-MIL-125(Ti)/PEBAX coated on PDMS/PSf were prepared in this work, and their gas separation performance for high CO2 feed gas was investigated under various operating circumstances, such as pressure and CO2 concentration, in mixed gas conditions. The functional groups and morphology of the prepared membranes were characterized by Fourier transform infrared spectroscopy (FTIR) and field emission scanning electron microscopy (FESEM). CO2 concentration and feed gas pressure were demonstrated to have a considerable impact on the CO2 and CH4 permeance, as well as the CO2/CH4 mixed gas selectivity of the resultant membrane. As CO2 concentration was raised from 14.5 vol to 70 vol , a trade-off between permeance and selectivity was found, as CO2 permeance increased by 136 and CO2/CH4 selectivity reduced by 42.17. The membrane produced in this work exhibited pressure durability up to 9 bar and adequate gas separation performance at feed gas conditions consisting of high CO2 content. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.